URGENSI PENERAPAN KEADAAN DIAM YANG BERLAKU SETELAH PENDAFTARAN PERMOHONAN PAILIT DI PENGADILAN NIAGA DALAM HUKUM KEPAILITAN INDONESIA - Claudio Shallaby Andre (2021)
Indonesian Bankruptcy Law through Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment (UU Kepailitan dan PKPU) still opens up opportunities both for debtor and creditor to commit actions that could harm either debtor or creditor while the bankruptcy examination is being conducted in the commercial court. The problems in this research are the impacts of the application of the automatic stay and the urgency of the application of the automatic stay which operates after the filing of the bankruptcy petition in the commercial court. This research is normative legal research. The problem approaches used in this research are the conceptual approach and the normative approach. This research found that UU Kepailitan dan PKPU still has the potential to harm both debtor and creditor when the bankruptcy examination is being conducted in the commercial court. In addition to that, the actio pauliana lawsuit and the petition for security seizure is not effective for protecting creditors. The results of the research are the application of the automatic stay has a detrimental impact on both debtor and creditor. It is also contrary to the legal protection theory, legal certainty, and creditor's bargain theory. To prevent the occurrence of acts committed by either debtor or creditor, UU Kepailitan dan PKPU may adopt the mechanism of the automatic stay that operates after the filing of the bankruptcy petition in the commercial.